Up-scaling orange-fleshed sweetpotato (Ipomoea batatas (L) Lam) technologies in western Kenya. - Ndolo, P.J.; McEwan, M.; Akhwale, M.; Odongo, M.; Nabiwa, G.; Yaite, B. (2012)
Vitamin A deficiency is a major nutritional problem in Kenya, leading to night blindness and high mortality rate in infants. Consumption of orange-fleshed sweetpotato (OFSP) that is high in -carotene (pro-vitamin A), can reduce the risk of the deficiency. The utilization of the OFSP in Kenya despite its nutritional advantage is limited. Efforts by the Government extension service to promote the crop has had limited impact. The Kenya Agricultural Research Institute in collaboration with the International Potato Centre and farmers developed a number of OFSP technologies that can enhance its utilization. The ASARECA/AfDB-supported project “Dissemination of New Agricultural Technologies in Africa” (DONATA) for Orange-fleshed sweetpotato (OFSP) was initiated in Bungoma and Busia counties of Western Kenya in 2008. The project used the Innovation Platforms for Technology Adoption (IPTAs) approach in up-scale the proven OFSP technologies. IPTA acts as the institutional mechanism bringing together different stakeholders for scaling out and scaling-up of OFSP technologies along the value chain. Within three years 29 technologies on seed systems, agronomic practises, postharvest processing and marketing were promoted to 7500 beneficiaries. This was achieved through training of 215 extension agents and 1250 farmers on different aspects of OFSP. Thirteen information products were made available to the users through 15 different uptake pathways. Area under OFSP root production increased by over 600% while productivity per unit area increased from 8 to 16 tons/ha in the project counties